Different length intertrial intervals in delayed matching-to-sample - SERRANO, MARIO; CAMACHO, ISAAC; CARPIO, CLAUDIO (Mexican Journal of Behavior Analysis, 2011)
Two groups of pigeons were exposed to a successive delayed matching-tosample procedure. For one group sample stimuli were differentially correlated with different length intertrial intervals, whereas for the other group the length of the intertrial interval was the same given either sample stimuli. For both groups precision index decreased as delay interval length increased; however, this effect was lesser for the group exposed to the procedure with different length intertrial intervals. Additionally, for this group only different local response rates at sample stimuli was observed. Results are discussed in relation to similar experiments, highlight the virtues of a parametric approximation to the experimental analysis of behavior in conditional discrimination situations.